Desenvolvimento e avaliação de tecnologias educacionais para prevenção de quedas em idosos - Lima, Rayanne Branco dos Santos (2018)
Falling is one of the leading causes of fatal or nonfatal injury in the elderly, accounting for 10% of emergency consultations of people over 65 years of age. It is estimated that by 2050 approximately one in three people aged 65 and over will suffer one or more falls per year, and about half of these will result in injuries. This study aimed to construct and evaluate two educational technologies for the prevention of falls in the elderly. Technology development study carried out between 2017 and 2018, in the City of Fortaleza, Ceará, Brazil. It was divided into two stages: Construction of Educational Technologies and Evaluation of Educational Technologies. The evaluation stage was carried out by 37 judges (21 evaluated the educational technology printed-serial album and 16 evaluated three-dimensional model-type technology). To evaluate the album we used an instrument built by the researchers, the Suitabillity Assesment of Materials (SAM), the Flesch readability index, the Content Validity Index and the Concordance Level. The model was evaluated by a specific instrument that allowed the evaluation of each room, furniture layout and cultural adaptation by the level of agreement. Both technologies were submitted to the pilot test based on the assumptions of the Nola Pender Health Promotion Model. The data were tabulated and analyzed in Microsoft Excel 2010. In the construction phase, fall prevention strategies were included in the album, such as: ideal shoes, walking on obstacle-free sidewalks, careful shopping, walking on public transport , with gardening and hiking. Already in the model, positive aspects were shown in the prevention as furniture arrangement and signaled the risks like carpets and obstacles by the house. In the evaluation stage, the judges considered the materials suitable for use in the prevention of falls in the elderly (I-CVI 0, 89, level of agreement between 92% and 94% for the serial album and between 86% and 89% for the model). The total Sam was 88, 23%. The Flesch index was 72%. It is concluded that the two technologies are suitable for use in the prevention of falls in the elderly, both in the home and abroad, however, new studies should be developed in clinical practice to consolidate the use of technologies as capable of promoting preventive actions facing the falls.